2020
DOI: 10.1108/jaee-07-2019-0147
|View full text |Cite
|
Sign up to set email alerts
|

Inventory management, managerial competence and financial performance of small businesses

Abstract: PurposeThe purpose of this study is twofold (1) to establish the relationship between inventory management, managerial competence and financial performance and (2) to test whether inventory management mediates the relationship between managerial competence and financial performance.Design/methodology/approachWe employed cross-sectional and correlational research designs. A questionnaire survey of 304 small businesses in Uganda was utilized. Hypotheses were tested using a bootstrap analysis technique with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 70 publications
4
68
0
10
Order By: Relevance
“…The impact is direct for managerial competences, and indirect for specialized competences and personal and social competences. The present findings correspond to the results emerging from the review of literature (Altinay and Wang, 2011;Orobia et al, 2020;Nakhata, 2007). The relationship between the competences and performance is logical and natural: the higher the management's competences the better performance is to be expected (Filipowicz, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The impact is direct for managerial competences, and indirect for specialized competences and personal and social competences. The present findings correspond to the results emerging from the review of literature (Altinay and Wang, 2011;Orobia et al, 2020;Nakhata, 2007). The relationship between the competences and performance is logical and natural: the higher the management's competences the better performance is to be expected (Filipowicz, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, respondents were expressly assured that there are no right or wrong answers as long as the responses are honest. This aimed at reducing the respondent's apprehension over their responses hence reducing the possibility of editing their answers to give what they perceive as the best answers (Orobia et al, 2020).…”
Section: Control For Common Methods Biasmentioning
confidence: 99%
“…Financial performance reflects a firm's ability to operate efficiently, profitably, grow, survive, and react to environmental opportunities and threats (Kamukama et al, 2017). In Africa, several businesses have collapsed, with poor financial performance cited as one of the leading causes of the collapse (Orobia et al, 2020). Specifically, in Uganda, businesses' poor financial performance is evident where 30% of companies do not survive beyond three years (Afunadula, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that business strategies mediate the consequence of material capability and performance of the firm. Orobia et al (2020) investigated the relationship between MM, managerial competence, and performance of 304 SMEs in Uganda, testing whether MM mediates the relationship between managerial competence and financial performance.…”
Section: Empirical Literaturementioning
confidence: 99%